Global perspectives of emerging occupational and environmental lung diseases. Issue 2 (March 2015) - Moitra, Subhabrata; Puri, Rajan; Paul, Devon; Huang, Yuh-Chin T.
Abstract : Purpose of review: New technologies continue to be introduced into the workplace and the environment. These novel technologies also bring in new hazards leading to evolving patterns of established occupational and environmental diseases, as well as novel conditions never before encountered. Recent findings: Many of these emerging conditions have appeared in media outlets or in the literature as case reports. These sentinel cases often serve as a warning sign for subsequent outbreaks. This review will discuss environmental and occupational lung diseases and exposures from a global perspective. These diseases and exposures include environmental exposure to asbestos and lung diseases, accelerated silicosis in sandblasting jean workers, coal worker's pneumoconiosis in surface coal miners, health effects of indoor air pollution from burning of biomass fuels and exposures to heavy metals and potential health effects from hydraulic fracturing (fracking). Other emerging conditions are also discussed, including smog in developing countries, sand storms in Asia and the Middle East and respiratory illnesses from nanoparticles and man-made fibres. Summary: Clinicians must remain vigilant for potential occupational and environmental exposures, especially when evaluating patients with unusual and unique presentation, so that occupational and environmental risk factors may be identified, and monitoring and preventive measures can be implemented early.